2016
DOI: 10.1007/s00280-016-3174-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic study of doxorubicin in children with cancer: results of a “European Pediatric Oncology Off-patents Medicines Consortium” trial

Abstract: PurposeDoxorubicin is a key component in many pediatric oncology treatment regimens; still pharmacology data on which current dosing regimens are based are very limited.MethodsWe conducted a multinational pharmacokinetic study investigating age dependency of doxorubicin metabolism and elimination in children with cancer. One hundred and one patients treated with doxorubicin according to a cancer-specific national or European therapeutic trial were recruited. Doses of doxorubicin ranged from 10.4 to 57.7 mg/m2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…TnI is more feasible than the other cardiac troponins for early CIC diagnosis due to its kinetic curve [18], but the exact dynamic of troponin release into bloodstream is not well known [5,12,19]. Although several papers have been published regarding CIC evaluation by troponin measurements, there are only a few studies on this subject in pediatric ALL setting [20][21][22][23][24][25][26][27][28][29]. Different groups monitored large cohorts of children with ALL and concluded that TnI was predictable for myocardial injury [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…TnI is more feasible than the other cardiac troponins for early CIC diagnosis due to its kinetic curve [18], but the exact dynamic of troponin release into bloodstream is not well known [5,12,19]. Although several papers have been published regarding CIC evaluation by troponin measurements, there are only a few studies on this subject in pediatric ALL setting [20][21][22][23][24][25][26][27][28][29]. Different groups monitored large cohorts of children with ALL and concluded that TnI was predictable for myocardial injury [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Krischke et al. showed in a PopPK model that children <3 years of age had a significantly lower clearance compared with older children even after correction for BSA, resulting in higher exposure in younger children . Additionally, Thompson et al.…”
Section: Admementioning
confidence: 99%
“…showed that doxorubicinol, an active metabolite of doxorubicin, was dependent on body composition: children with >30% body fat showed a significantly lower clearance of doxorubicinol, with a mean of 37 L/h/m² compared with 64 L/h/m² for <30% body fat; however, the groups were small. The metabolite doxorubicinol may contribute to the cardiotoxicity after doxorubicin administration …”
Section: Admementioning
confidence: 99%
See 2 more Smart Citations